Assessment of chest CT abnormalities and pulmonary function at 6-month and 1-year after hospital discharge in Chinese patients of COVID-19 pneumonia at the turn of 2022–2023 - Fang, Xingyu; Li, Jialin; Zhang, Yijun; Lv, Wei; Liu, Lin; Feng, Yun; Liu, Li; Pan, Feng; Zhang, Jinping (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to assess chest CT abnormalities and pulmonary function at 6-month and 1-year follow-ups in coronavirus disease 2019 (COVID-19) pneumonia patients of the China epidemic in the turn of 2022–2023.MethodsA total of 156 hospitalized patients with COVID-19 pneumonia admitted between 29 November 2022 and 10 February 2023 were prospectively assessed at 6-month and 1-year follow-ups. Characteristics and CT scores of pulmonary abnormalities and pulmonary function were compared between different follow-up time points. The correlation of CT abnormalities and pulmonary function at 1-year were evaluated.ResultsOver 1 year, the proportion of pulmonary abnormalities gradually decreased (initial, 100%, 156/156; 6-month, 57.1%, 89/156; and 1-year, 37.8%, 59/156; P < 0.001), whereas fibrotic changes increased (initial, 6.4%, 10/156; 6-month, 14.1%, 22/156; and 1-year, 14.7%, 23/56; P < 0.001). Compared to participants of the subgroup with nonfibrotic changes, diffusion capacity of the lung for carbon monoxide (DLCO)(P = 0.01) and DLCO less than 80% predicted (P < 0.001) showed significantly decrease in participants of the subgroup with fibrotic changes. The extent of fibrotic changes was strongly correlated with lower DLCO (r = −0.734, P < 0.001).ConclusionFibrotic changes might show a tendency to persist over time and correlate strongly with impairment of diffusion function, thus requiring more attention in future follow-ups.